(3GdCWQGas - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3jHJOF HMOjK YWGA GdeOjfi ehdi Ce UHjI GdLgfjI Yf CHj gQjQI (B: (3dhdG Cf CTb Ydi CeJi dCeQJge HGdShGc s
(3BNQgG (B:s
(3hjfJgi HMOjK (B: (3CHj SGFQ CRhGL GdfHi Udi Gddg Ydjg hSde Cf jONd Ydjge HJdc GdhVGYI hgh BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3fbdJ Yf NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs